2010
DOI: 10.1371/journal.pone.0012328
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Triggered Aggregation of Copper, Zinc Superoxide Dismutase in the Presence of Ascorbate

Abstract: The oxidative damage hypothesis proposed for the function gain of copper, zinc superoxide dismutase (SOD1) maintains that both mutant and wild-type (WT) SOD1 catalyze reactions with abnormal substrates that damage cellular components critical for viability of the affected cells. However, whether the oxidative damage of SOD1 is involved in the formation of aggregates rich in SOD1 or not remains elusive. Here, we sought to explore the oxidative aggregation of WT SOD1 exposed to environments containing both ascor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…Furthermore, increased levels of carbonylated aggregates are observed in patients with age-related disorders such as Parkinson's disease, Alzheimer's disease and cancer. Even wild-type Sod1p is prone to oxidative destabilization and aggregation in vitro [59,100], consistent with this protein's susceptibility to carbonylation (see the section entitled 'Protein oxidation'). Even wild-type Sod1p is prone to oxidative destabilization and aggregation in vitro [59,100], consistent with this protein's susceptibility to carbonylation (see the section entitled 'Protein oxidation').…”
Section: Formation Of Toxic Protein Aggregatessupporting
confidence: 57%
“…Furthermore, increased levels of carbonylated aggregates are observed in patients with age-related disorders such as Parkinson's disease, Alzheimer's disease and cancer. Even wild-type Sod1p is prone to oxidative destabilization and aggregation in vitro [59,100], consistent with this protein's susceptibility to carbonylation (see the section entitled 'Protein oxidation'). Even wild-type Sod1p is prone to oxidative destabilization and aggregation in vitro [59,100], consistent with this protein's susceptibility to carbonylation (see the section entitled 'Protein oxidation').…”
Section: Formation Of Toxic Protein Aggregatessupporting
confidence: 57%
“…The report that the proteinaceous inclusions as a hallmark of ALS do not have the classic fibrillar appearance of amyloid prompted us to examine morphology of the A4V SOD1 aggregates formed with polyanions under TEM. The aggregates of both wtSOD1 and its oxidized form in the presence of DNA were observed to have the heterogeneous profiles similar to those identified in the diseased neurons and tissues under acidic and neutral conditions …”
Section: Resultssupporting
confidence: 52%
“…Although an increase in the extrinsic thioflavin T (ThT) fluorescence is a well-used method to characterize the formation of fibrillar protein amyloids, the increased ThT signal caused by the formation of amyloid fibrils cannot be used to monitor the formation of protein aggregates with DNA, not only because of the formation of non-fibrillar protein aggregates in the presence of DNA, but also because the ThT signal increased by interactions with DNA can mask the ThT signal enhanced by protein aggregation. [43][44][45] To prove the availability of Trp fluorescence to follow the aggregation with polyanions, first, the time course of A4V aggregation in the presence of LMWHep was simultaneously monitored with three methods at pH 4.0, because the presence of LMWHep does not affect ThT fluorescence. The data showed that following a lag phase of 20 s, Trp fluorescence was quenched with incubation time, whereas both ThT fluorescence and LS value were enhanced [ Fig.…”
Section: Acceleration Of A4v Aggregationmentioning
confidence: 99%
See 2 more Smart Citations